Empire as the triumph of theory : imperialism, information, and the Colonial Society of 1868 - Beasley, Edward, 1964- (Routledge, 2005)
A key addition to our understanding of the Victorian-era British Empire, this book looks at the founders of the Colonial Society and the ideas that led them down the path to imperialism.
Title from PDF title page (viewed 3 Dec., 2009).
Keywords: Colonial Society (Great Britain); Imperialism -- History -- 19th century.; Great Britain -- Colonies -- History -- 19th century.; Impérialisme -- Histoire -- 19e siècle.; Grande-Bretagne -- Colonies -- Histoire -- 19e siècle.; POLITICAL SCIENCE -- Colonialism & Post-Colonialism.; British colonies; Imperialism; 1800-1899; Multi-User: limited to 5 simultaneous users.; Electronic books.; History